eBantu Solat 2D Animation Mobile Application: A Mobile Application as a Guidance to Perform Wudhu and Prayers During Illness - Ghazali, Nurul Syazwani; Sulaiman, Suzidiana (Journal of Computing Technologies and Creative Content, 2021)
Prayers are the most important act of worship in the life of a Muslim, whether they are in good health, in pain, or otherwise. “Allah does not burden an individual except in accordance with his willingness and ability,” says God in Surah Al Baqarah verse 286. That is to say, prayers should not be taken lightly. The invention of the Android smart phone is one of the most rapid advancements in telecommunication technology. With a wide range of features and apps, smart phones can be used for more than just communication. They can also be used to meet a variety of human needs, such as entertainment and learning aids. As a result, some Muslims have less time to read books or study religious science, especially the science of wudhu’ and prayer. Some of us are unaware of the proper wudhu’ and prayer procedures as prescribed by the Quran and Sunnah. As a result, the aim of this study is to design and create a mobile prayer and wudhu guide in the form of a 2D animation video that teaches users how to pray correctly in a crisis. The aim of this study was to determine the factors that influence the usage of the eBantu Solat mobile application. As a consequence of the results, this study aids in improving the quality of product production by ensuring that research techniques and writing are correctly understood. This app is also very useful for Muslims in recognising the proper and correct way to pray during illness.